Self-assembled nanostructures of L-ascorbic acid alkyl esters support monomeric amphotericin B - Nocelli, Natalia Estefanía (2021)
Amphotericin B (AmB) is a highly effective antimicrobial, with broad antimycotic and antiparasitic effect. However, AmB poor water-solubilisation and aggregation tendency limits its use for topical applications. We studied the capacity of nanostructures formed by alkyl esters of L-ascorbic acid (ASCn) to solubilise AmB and tested the relationship between the prevalence of the monomeric form of AmB and its effectiveness as antimicrobial agent.